«Que coisa é a verdade?»: Theatrum mundi e o mistério da existência no Acto da Primavera de Manoel de Oliveira (1963) - Lopes, Maria Inês; Rebelo, João (CEM – Cultura, Espaço & Memória, 2020)
The moving image and the visual culture lay down a field of references between imaginary and projected image. Rite of Spring (a Manoel de Oliveira feature film from 1963) is a good exemple of this relationship. If, by one hand, it inaugurates inquisitive tools that will turn into recurring issues in the author’s vision of cinema, by stressing the distance between image and médium, by the theatricality of the performance and by the operative relationship constructed between rhythm and film editing, on the other hand, this film is also an excelent essay on the action of images, when confronted with the christian imaginary that we inherited through visual culture and ritual. This way, we propose to analyze Manoel de Oliveira’s Rite of Spring as a device for the comprehension of life’s theatricallity, and as game of mirrors with our mental images as well.